2017
DOI: 10.1186/s12909-017-1095-9
|View full text |Cite|
|
Sign up to set email alerts
|

Risk factors associated with academic difficulty in an Australian regionally located medical school

Abstract: BackgroundDespite the highly selective admission processes utilised by medical schools, a significant cohort of medical students still face academic difficulties and are at a higher risk of delayed graduation or outright dismissal.MethodsThis study used survival analysis to identify the non-academic and academic risk factors (and their relative risks) associated with academic difficulty at a regionally located medical school. Retrospective non-academic and academic entry data for all medical students who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
0
13
0
3
Order By: Relevance
“…In spite of this effective academic support system, about 16% of the students in the JCU MBBS course experience academic difficulty, while 3% of these students fail and exit the program [12]. Therefore, there is a need to understand the characteristics and functioning of the failing medical students to better support them.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this effective academic support system, about 16% of the students in the JCU MBBS course experience academic difficulty, while 3% of these students fail and exit the program [12]. Therefore, there is a need to understand the characteristics and functioning of the failing medical students to better support them.…”
Section: Introductionmentioning
confidence: 99%
“…A prior systematic review reported several factors that could affect medical students' academic success, including previous academic performance, and cognitive ability [3]. Studies have also reported associations between demographic factors, such as gender and age, and students' academic performance and/or dropout rate [4][5][6][7][8][9][10]. Furthermore, contextual factors such as type of school (e.g., state-funded schools vs. independent schools) [11] and hometown (rural or remote vs. metropolitan areas) [4,12] have been linked to student academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear why medical students who belonged to a neighborhood HS have better chance of passing the NMLE, and we found no such study on the relationship between NMLE and the location of HS or hometown. Given previous study on academic performance [ 16 , 18 ], students from the neighborhood city/town might be able to receive various kinds of supports from their families physically, economically, and psychologically. Further investigations are required.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies did not confirm their results using predictors in a new group of students. Previous studies about medical students’ academic success reported academic performance associated with not only post admission variables such as previous academic performance [ 15 , 16 ] and Objective Structured Clinical Examination (OSCE) [ 17 ], but also pre-admission variables such as gender [ 17 ], age at admission [ 16 ], hometown [ 16 , 18 ], type of high school (HS) [ 19 ], HS grade point average (GPA) [ 20 ], and entrance exam for medical schools [ 21 ].…”
Section: Introductionmentioning
confidence: 99%